THE QUADRO HELIX COMMUNICATION MODELS APPROACH IN DEVELOPING CREATIVE CITY OF MALANG - Ardhanariswari, Kartika Ayu; Prayudi, .; Probosari, Ninik (PEOPLE: International Journal of Social Sciences, 2021)
The development of the creative economy as the basis for the city’s growth has given rise to a creative city concept. Cities are a vehicle for residents to move, innovate, and be creative. To foster creative behavior in the city economy requires continuous communication and support from all stakeholders, including Government, economic actors, and society. The first parameter of a creative city is that it can develop the potential for a creative economy. Second, there is a role and synergy between the government, academics, business actors, and the community (community). This research aims to produce multi-stakeholder communication models based on the Quadro Helix approach by Malang creative city. This methodology research will be conducted using qualitative methods through in-depth interviews, observation, and Focus Group Discussion (FGD) on government, academics, business actors, society (community). The result found that Communication synergy between the government, business, community, and academics is essential in developing Malang as a Creative City. The quadrohelix stakeholders are united in the creative Economy Committee, which helps formulate a roadmap for Malang as a creative city.